Synergistic effect of citric acid and carbon dots modified g-C3N4 for enhancing photocatalytic reduction of Cr(VI) - Jiamin Liu (IWA Publishing, 2021)
Carbon dot (CD)-modified graphitic carbon nitride (g-C3N4) photocatalysts were synthesized through a one-step homogeneous thermal pyrolysis. The synergetic effect of citric acid (Cit) and g-C3N4/CDs for high-performance visible light Cr(VI) photocatalytic reduction had been investigated. Cit was not only acted as a hole scavenger, but might also form surface charge transfer complexes (CTC) with g-C3N4 which delivered electrons on the Highest Occupied Molecular Orbital (HOMO) of Cit to the conduction band (CB) of g-C3N4. CDs decorated on g-C3N4 could provide channels for the preferential transfer of electrons on CTC to the CB of g-C3N4 as well as improved separation of the charge carriers. Owing to these synergistic effects, g-C3N4/CDs displayed much higher photocatalytic performance for the reduction of Cr(VI), which was 1.89 times higher than g-C3N4. Moreover, the synergetic photocatalytic reduction mechanisms of aqueous Cr(VI) were proposed to elucidate the active species formation and photogenerated electron transfer. The results suggested that the in situ generated hydrogen peroxide (H2O2) dominated the reduction of Cr(VI). The addition of Cit could trigger the in situ generation of H2O2 and the decorated CDs further enhanced the reaction. This work demonstrated the role of widely existed Cit on the photocatalytic reduction of Cr(VI) in natural aquatic environment. HIGHLIGHTS g-C3N4/CD photocatalysts were synthesized for Cr(VI) reduction.; CDs promoted light harvest and improved the separation of charge carriers.; Cit triggered the visible light photocatalytic reduction of Cr(VI) over g-C3N4/CDs.; H2O2 is the main effective activator for Cr(VI) reduction in the g-C3N4/Cit system.; The photocatalytic reduction pathways of Cr(VI) in the presence of cit were proposed.;